إدارة الإنفاق الحكومي بين الترشيد والتخفيض - سليمان، علي شهاب; صابوني، جميل عبدالرحمن (جامعة البعث, 2022)
يعتبر موضوع إدارة الإنفاق الحكومي من المواضيع التي تحظى باهتمام كبير لدى حكومات الدول النامية منها والمتقدمة على حد سواء، فالأزمات الاقتصادية التي ألمت بها وما رافقها من انخفاض حاد في حجم الإيرادات العامة، كانت الدافع الرئيسي لدى المعنيين في تلك الدول للبحث في شتى السبل الممكنة لإدارة تلك الموارد، وأنفاقها ضمن ضوابط معينة تمكنها من حيث النتيجة من تجاوز تلك الأزمات. إن إدارة الإنفاق الحكومي، وما تنطوي عليه من أدوات، وكذلك ما تتطلبه هذه الإدارة من ظروف وعوامل مساعدة لنجاحها؛ إنما تعتبر في الوقت الراهن حاجة ملحة لإعادة التوازن والاستقرار ما أمكن ذلك إلى الهياكل الاقتصادية للدول، والتي أنهكت أصلا نتيجة تواتر الأزمات التي ألمت بها، فالتخصيص الأمثل للموارد المالية المتاحة، وتحقيق الكفاءة في استخدامها بين قطاعات الدولة المختلفة، قد أصبح اليوم نهجا أحوج ما نكون إليه لتقليص الفجوة الحقيقية بين الموارد المتاحة والإنفاق المطلوب، وذلك في إطار تحقيق التنمية الشاملة وترسيخ دعائم الاستقرار الاقتصادي. The issue of government spending management is one of the topics of great interest to the governments of developing and developed countries alike. The economic crises that have befallen them and the accompanying sharp decline in the volume of public revenues, were the main motive for those concerned in those countries to search for various possible ways to manage Those resources, and spending them within certain controls that enable them, in terms of the outcome, to overcome those crises. The management of government spending, and the tools involved, as well as the conditions and factors that help this administration require its success; Rather, it is considered at the present time an urgent need to restore balance and stability as possible to the economic structures of countries, which were already exhausted as a result of the recurring crises that have befallen them. The optimal allocation of available financial resources, and achieving efficiency in their use among the various sectors of the state, has become today an approach that is in need of what we are To reduce the real gap between the available resources and the required spending, within the framework of achieving comprehensive development and consolidating the foundations of economic stability.
Keywords: السياسات الاقتصادية -- الاستقرار الاقتصادي -- المالية العامة